Crop Diversification Analysis at the Farm Level: Empirical Evidence from Different Regions of Uzbekistan - Abdulla Primov (ZBW – Leibniz Information Centre for Economics, 2025)
In Uzbekistan, land is more appropriate for cultivating fruits and vegetables. Since independence, the government of Uzbekistan has implemented a number of agricultural policies such as making some crucial structural reforms at the farms, comprising different institutions and enhancing diversification of agricultural production in order to stabilize on agricultural sector of the country. Therefore, crop diversity has an important role in sustainable agriculture. The main objective of the study is to analyze the degree and extent of crop diversification among farmers. We calculated the diversification index based on the Simpson Diversity Index method. The study revealed the mean computed Simpson Index values indicate that diversity index was found 0.59, 0.45, 0.56 and 0.62 for Andijan, Karakalpakstan, Kashkadarya and Tashkent regions, respectively. This implies that Tashkent region farmers shifted towards more diversification cropping patterns than other counterparts of the country. The overall result in the four states combined in this study reveals a mean Simpson Index within the sample of farmers was 0.56. This suggests that the farmers in the study areas were not too diversified in their cropping pattern. While cultivating several crop species also helps the farmers to manage both price and production risks which attains more food options for the household and income through marketing the produce from the surpluses.
Keywords: Q1; D13; D31; O18; 330; Crop diversification; Simpson Diversification Index; Cropping patterns; Uzbekistan